Effects of Soil Conditions on Cost of Low Head SHP Schemes - Singal, Sunil K.; Saini, R. P.; Raghuvanshi, C. S. (Hydro Nepal: Journal of Water, Energy and Environment, 2011)
Energy is the engine of growth of any developing economy. Consumption of electrical energy is universally accepted indicator of progress in the agricultural, industrial and commercial sectors, as also of the well being of the people of the nation. India is blessed with many rivers, natural streams, canal networks and mountains offering tremendous small hydropower potential which is clean and technically proven source of energy. Under this study, an attempt has been made to discuss the cost sensitive parameters of small hydropower schemes. Based on the cost sensitive parameters, the methodology for estimation of cost of low head small hydropower scheme has been evolved and the effect of soil conditions on cost of SHP schemes discussed. DOI: http://dx.doi.org/10.3126/hn.v8i0.4904 Hydro Nepal: Journal of Water, Energy and Environment Issue No. 8, 2011 January Page: 24-28 Uploaded date: 16 June, 2011